Calculation aspects of the European Rebalanced Basket Option using Monte Carlo methods - Van der Merwe, Carel Johannes (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MComm (Statistics and Actuarial Science)--University of Stellenbosch, 2010.